A fast Myosin super enhancer dictates muscle fiber phenotype through competitive interactions with Myosin genes - Matthieu Dos Santos; Stéphanie Backer; Frédéric Auradé; Matthew Man-Kin Wong; Maud Wurmser; Rémi Pierre; Francina Langa; Marcio Do Cruzeiro; Alain Schmitt; Jean-Paul Concordet; Athanassia Sotiropoulos; F. Jeffrey Dilworth; et al. (Nature Communications, 2022)
The contractile properties of adult myofibers are shaped by their Myosin heavy chain isoform content. Here the authors show that a super enhancer controls the spatiotemporal expression of the genes at the fast myosin heavy chain locus by DNA looping and that this expression profile is recapitulated in a rainbow transgenic mouse model of the locus.